The Cossidae (Lepidoptera) of Afghanistan with description of three new species and special notes on the fauna of Bande-Amir National Park - Yakovlev, Roman V.; Pljustch, Igor G.; Skrylnik, Yuriy; Pak, Oleg; Witt, Thomas J. (Zootaxa, 2015)
The annotated list of Cossidae of Afghanistan consists of 44 species in 17 genera from the four subfamilies Catoptinae, Cossinae, Zeuzerinae, and Mehariinae. Three new species are described: Cossulus habibae Yakovlev, Pljustch, Skrylnik & Pak, sp. nov., Semagystia bamiani Yakovlev, Pljustch, Skrylnik & Pak, sp. nov., Phragmacossia bandeamiri Yakovlev, Pljustch, Skrylnik & Pak, sp. nov.; all from Band-e-Amir National Park in Bamian Province. Three species (Dervishiya cadambae (Moore, 1865), Semagystia cossoides (Graeser, 1892), Phragmacossia territa (Staudinger, 1879)) are reported for the first time from Afghanistan. A brief biogeographical analysis of the Cossidae of Afghanistan is given.